2011
DOI: 10.4314/ejb.v13i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture conditions of Streptomyces rochei (MTCC 10109) for the production of antimicrobial metabolites

Abstract: Fermentation and culture conditions were studied in shaken-flask culture to induce the production of greater amounts of antimicrobial metabolites by Streptomyces rochei (10109). Antimicrobial metabolite production started after 48 h incubation and reached its optimum level at 20% inoculum size at 120 h, at which point the metabolites showed maximum antifungal and antibacterial activity against selected human pathogenic microorganisms (Candida albicans, Staphylococcus aureus and Escherichia coli). Optimal produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…The cell free supernatant thus obtained was concentrated five-fold in the vacuum concentrator and 50 µl was used to determine antimicrobial activity. The diameters of zones of inhibition were noted [11].…”
Section: Effect Of Incubation Periodmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell free supernatant thus obtained was concentrated five-fold in the vacuum concentrator and 50 µl was used to determine antimicrobial activity. The diameters of zones of inhibition were noted [11].…”
Section: Effect Of Incubation Periodmentioning
confidence: 99%
“…Actinomycete cell metabolism under conditions of nutritional excess is known to be directed towards the generation of cell mass rather than production of secondary metabolites. Also, glucose is known to cause catabolite repression, in which production of enzymes of secondary metabolite bio-synthesis is inhibited [11] [20]. It has been observed that secondary metabolite production is often stimulated by slowly assimilated complex carbon sources like polysaccharides [21].…”
Section: Effect Of Carbon Sources On Growth and Bioactive Metabolite mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary metabolite production is often stimulated by slowly assimilated complex carbon sources like polysaccharides. A possible explanation for this phenomenon is that glucose causes catabolite repression, in which production of enzymes of secondary metabolite biosynthesis is inhibited 7,[23][24] . Starch has been found to be the best carbon source for antibiotic production by Gao et al 25 .…”
Section: Molecular Identification Of the Isolatementioning
confidence: 99%
“…Changes in the nature and type of carbon and nitrogen sources have been reported to affect antibiotic biosynthesis in Streptomyces [6][7] . Also several cultivation parameters like pH, incubation period and temperature play a major role in the production of bioactive metabolites 8 .…”
mentioning
confidence: 99%